2005
DOI: 10.1002/art.21452
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of a multidisciplinary job‐retention vocational rehabilitation program with usual outpatient care in patients with chronic arthritis at risk for job loss

Abstract: Objective. Work disability is a major consequence of inflammatory rheumatic conditions. Evidence regarding the effectiveness of interventions aimed at the prevention or reduction of work disability in rheumatic diseases is limited. We conducted a randomized controlled trial to investigate the effectiveness of a multidisciplinary job-retention vocational rehabilitation (VR) program in patients with a rheumatic condition who were at risk for job loss. Methods. A total of 140 patients with a chronic rheumatic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 34 publications
(31 reference statements)
4
48
0
1
Order By: Relevance
“…In a previous analysis of our study, we showed that a multidisciplinary job retention vocational rehabilitation program led to a greater improvement of fatigue levels and mental health, but without significant reduction of job loss (17). The purpose of the present study was to estimate, from a societal perspective, the cost-utility of the program for patients with chronic rheumatic diseases at risk of job loss.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…In a previous analysis of our study, we showed that a multidisciplinary job retention vocational rehabilitation program led to a greater improvement of fatigue levels and mental health, but without significant reduction of job loss (17). The purpose of the present study was to estimate, from a societal perspective, the cost-utility of the program for patients with chronic rheumatic diseases at risk of job loss.…”
Section: Introductionmentioning
confidence: 84%
“…Only 1 in 15 patients consulted a psychologist. The program led to a greater improvement of fatigue levels and mental health, but no reduction of job loss was established (17). In the economic evaluation reported here, we studied whether, from the societal perspective, effectiveness is attained with reasonable costs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations